Analisis Maqashid Syariah dalam Transaksi Akad Qiradh - Akmal, Haerul; Marjany, Nawa; Islam, Muhammad Thoriqul; Muthoharoh, Intan (Universitas Islam Lamongan, 2024)
Buying and selling is one of the most important activities in a human's life. Imam Madzahib Arba'ah has a very deep concern in the problem of buying and selling, including to the Qiradh. This study aims to determine the implementation of maqashid sharia contained in the implementation of the qiradh, In the view of Imam Madzahib Arba'ah, they are Imam Abu Hanifah, Imam Malik, Imam Syafi'i and Imam Ahmad. This type of research is qualitative research, while the analysis method used is content analysis, that way researchers can be find the concept of Maqashid Sharia contained in the Qiradh. The results of this study indicate that in this Qiradh contract, there are two concepts of maqashid sharia, firstly is preservation of the offspring and secondly is preservation of wealth. The conclusion of this study is that the preservation of the offspring is described in the willingness of the muqrid to help others, with their wealth. And in the preservation of wealth, it is discribed in the distribution of assets carried out by the muqrid to the muqtarid. This research is expected to be a contribution to the development of micro and macro financial institutions by prioritizing the Qiradh contract as one of the superior products.